ANALISIS KEPUASAN MASYARAKAT TERHADAP WAJIB BELAJAR SEMBILAN TAHUN DI PROVINSI BALI - Suwiti, NK; Bendesa, IKG; Sudibia, IK; Suyana Utama, IM; Budiarsa Suyasa, IW (PIRAMIDA; Vol. 7, No. 2 Desember 2011, 2012)
Compulsory education is the minimum educational programs must be followed byIndonesian citizen and the responsibility by local government. This program has beenmanifested in Government Regulation Republik of Indonesia Number 47 in 2008. Thepurpose of the study to analyze the public response to the implementation of nine-yearcompulsory education, especially in Bali Province. Research variables are : 1).Implementation of the educational curriculum 2) Teaching and learning process, 3).Learning facilities, 4). Realization of the program 5). Students learning outcomes. Theresearch data were sourced from Denpasar, Badung, Karangasem and Buleleng regency, thenumber of samples are 400 persons. The results showed, that all of the variable in goodcategory, Teaching and learning process variable have the better catagory, while gettingthe bad category are learning facilities variable. The analysis showed that the communitysatisfaction of the nine-year compulsory education did no association relationship onregency in Bali province, but positive associated with age of respondens. Results of thisstudy can be input to governments, should be improvements in the implementation of nineyearcompulsory education.
Keywords: Nine-year Compulsory education, Bali Province, Educational curriculum.